Q Fever: Current State of Knowledge and Perspectives of Research of a Neglected Zoonosis - Sarah Rebecca Porter; Guy Czaplicki; Jacques Mainil; Raphaël Guattéo; Claude Saegerman (International Journal of Microbiology)
Q fever is an ubiquitous zoonosis caused by an resistant intracellular bacterium, Coxiella burnetii. In certain areas, Q fever can be a severe public health problem, and awareness of the disease must be promoted worldwide. Nevertheless, knowledge of Coxiella burnetii remains limited to this day. Its resistant (intracellular and environmental) and infectious properties have been poorly investigated. Further understanding of the interactions between the infected host and the bacteria is necessary. Domestic ruminants are considered as the main reservoir of bacteria. Infected animals shed highly infectious organisms in milk, feces, urine, vaginal mucus, and, very importantly, birth products. Inhalation is the main route of infection. Frequently asymptomatic in humans and animals, Q fever can cause acute or chronic infections. Financial consequences of infection can be dramatic at herd level. Vaccination with inactive whole-cell bacteria has been performed and proved effective in humans and animals. However, inactive whole-cell vaccines present several defects. Recombinant vaccines have been developed in experimental conditions and have great potential for the future. Q fever is a challenging disease for scientists as significant further investigations are necessary. Great research opportunities are available to reach a better understanding and thus a better prevention and control of the infection.